4‐2: From the Synthesis of High‐Quality InP‐based Quantum Dots to the Development of Efficient QD Light‐Emitting Diodes. Issue 1 (30th May 2018) - Wedel, Armin; Kim, Yohan; Heyne, Benjamin; Geßner, André
Abstract : Environmentally friendly InP‐based colloidal quantum dots (QDs) have been intensively researched for the application of color‐saturated display and lighting application due to the potential impacts based on the unique properties of QDs itself. In this paper, we present our development on QD synthesis and QD light‐emitting diodes (QLEDs, or QD‐LEDs).